Changes in library spaces after Covid-19 restrictions - Gallo-León, José-Pablo (Anuario ThinkEPI, 2022)
The restrictions experienced during the Covid-19 pandemic have changed the use of library spaces, potentially affecting their design and even the need for them. We still lack conclusive data to know if library usage will recover. However, professional opinions note that, although digitization will be reinforced, face-to-face attendance will continue to be necessary. There are no examples of libraries planned according to the experiences of the pandemic, but everything seems to indicate that previous architectural trends have been strengthened or will continue to be so.